Home Self-collection to test for Human Papillomavirus and Chlamydia trachomatis infection in riverside women in Amazonas (Research, Society and Development, 2023)
Women living in rural areas of Amazonas - the riverine - have difficulty accessing adequate health care, aggravating their vulnerability in the face of various pathological processes, such as cervical cancer and sexually transmitted infections. Strategies that expand coverage of screening and early diagnosis are welcome. To evaluate the prevalence of Human Papillomavirus (HPV) and Chlamydia trachomatis (CT) in riverside women from Coari City, Amazonas, in samples obtained by self-collection and to verify the acceptance of this method among the participants. Fifty eight riverside communities were visited, with a “house-to-house” approach. The samples were obtained with a COARI® brush (Kolplast®) and the diagnosis of pathogens was made by Polymerase Chain Reaction. Four hundred and nineteen sexually active women aged between 18 and 70 years old (34.4 ± 12.1) participated in the study. The prevalence of CT in this population sample was 1.1% and that of HPV was 15.7%. We observed a low prevalence of CT and a high prevalence of HPV among participating women, in addition to a good acceptance of self-collection among them.